1997
DOI: 10.1128/aem.63.2.567-573.1997
|View full text |Cite
|
Sign up to set email alerts
|

L-Arogenate Is a Chemoattractant Which Can Be Utilized as the Sole Source of Carbon and Nitrogen by Pseudomonas aeruginosa

Abstract: L-Arogenate is a commonplace amino acid in nature in consideration of its role as a ubiquitous precursor of L-phenylalanine and/or L-tyrosine. However, the questions of whether it serves as a chemoattractant molecule and whether it can serve as a substrate for catabolism have never been studied. We found that Pseudomonas aeruginosa recognizes L-arogenate as a chemoattractant molecule which can be utilized as a source of both carbon and nitrogen. Mutants lacking expression of either cyclohexadienyl dehydratase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…38 (4-Hydroxy-3,5-diiodophenyl)pyruvic acid 70 was subjected to the previously described oxygenation conditions and the resulting complex product Work carried out with Pseudomonas aeruginosa has recently shown that arogenate 79 acts as a chemoattractant and can be utilised as a sole carbon and nitrogen source. 39 The major catabolic route has been proposed to involve the initial transamination of arogenate to prephenate in the periplasm by an aromatic aminotransferase followed by transport into the cytoplasm (Scheme 20). Here it is substrate for cyclohexadienyl dehydrogenase which yields 4-hydroxyphenylpyruvate and leads on through 4-hydroxyphenylacetate and 3,4-dihydroxyphenylacetate with a subsequent ring cleavage giving rise to a catabolite which can feed into the tricarboxylic acid cycle.…”
Section: Thyroxinementioning
confidence: 99%
“…38 (4-Hydroxy-3,5-diiodophenyl)pyruvic acid 70 was subjected to the previously described oxygenation conditions and the resulting complex product Work carried out with Pseudomonas aeruginosa has recently shown that arogenate 79 acts as a chemoattractant and can be utilised as a sole carbon and nitrogen source. 39 The major catabolic route has been proposed to involve the initial transamination of arogenate to prephenate in the periplasm by an aromatic aminotransferase followed by transport into the cytoplasm (Scheme 20). Here it is substrate for cyclohexadienyl dehydrogenase which yields 4-hydroxyphenylpyruvate and leads on through 4-hydroxyphenylacetate and 3,4-dihydroxyphenylacetate with a subsequent ring cleavage giving rise to a catabolite which can feed into the tricarboxylic acid cycle.…”
Section: Thyroxinementioning
confidence: 99%
“…In contrast to L -phenylalanine and L -tyrosine, catabolism of the closely related L -arogenate has been shown not to depend upon expression of phhC (Fischer et al, 1997). Although L -arogenate can be catabolized through conversion to L -phenylalanine via periplasmic cyclo- hexadienyl dehydratase (in which case PhhC would be functional), an alternative and more robust pathway to 4-hydroxyphenylpyruvate apparently exists via its conversion to prephenate by oxidative deamination.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies reported that P. aeruginosa is attracted by different amino acids, organic acids, aromatic compounds, sugars, oligopeptides, phytohormones, or inorganic compounds (24)(25)(26)(27)(28)(29)(30)(31) and repelled by other compounds, including chloroform and (11). 4HB, four helix bundle; Cache, calcium channels and chemotaxis receptors; HBM, helical bimodular; PilJ, N-terminal domain of type IV pilus chemoreceptor; NIT, nitrate and nitrite sensing; PAS, Per-Arnt-Sim.…”
Section: Molecular Mechanisms and Chemoreceptors For Chemotaxismentioning
confidence: 99%